Investigation of a nonlinear difference equation in a Banach space in a neighborhood of a quasiperiodic solution - Samoilenko, A. M.; Slyusarchuk, V. E.; Slyusarchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We investigate the behavior of a diserete dynamical system in a neighborhood of a quasiperiodic trajeetory for the case of an infinite-dimensional Banach space We find conditions sufficient for the system considered to reduce, in such a neighborhood, to a system with quasiperiodic coefficients.